The Management of Public Facilities Area in Sidomakmur Baru Complex Dau Sub District Malang Regency as a Community Hall and Playground - Bayu Teguh Ujianto; Redi Sigit Febrianto; Tutut Nani Prihatmi (Green Visioneers, 2021)
According to Government Regulation No. 14/2016, every housing and settlement area is required to provide facilities and infrastructure and public facilities. However, in Sidomakmur Baru Complex, the developer has provided the facilities only in the form of empty land that has not been adequately processed and serves only as a water catchment area. The land will be very potential if processed into a place that can accommodate more functional community activities, such as processing its function as a Citizen Hall and Playground for children. Manage the function of the land while maintaining its previous function as a water catchment area. The method used in this activity was field observation and advance plan and a participatory action research strategy. In terms of design, the main focus is to have a decent architecture while still paying attention to the surrounding environment.